Changes in sleep quantity and efficiency in professional rugby union players during home-based training and match play - Eagles, A. N.; Lovell, D. I. (The Journal of Sports Medicine and Physical Fitness, 2016)
Adequate sleep is paramount to athlete recovery and performance, however little is know about the typical sleep patterns of professional rugby union players during home based training and match-play in the competitive season.